Reverend Dr. Martin Luther King, Jr. March in Downtown Fresno to Saroyan Theatre - Watkins, Howard::::::::: (1985)
June Loring with yellow plaid cover, Jacqueline Pillar, Carolyn Murphy, Dale Doig ?,?, Linda Mack looking away